Tandem Mass Spectrometry for Polymeric Structure Analysis: A Comparison of Two Common MALDI–ToF/ToF Techniques. Issue 13 (8th May 2019) - Town, James S.; Jones, Glen R.; Hancox, Ellis; Shegiwal, Ataulla; Haddleton, David M.
Abstract: Tandem mass spectrometry is a powerful technique for investigating polymer architecture. However, in‐depth studies of the technique for polymers is relatively lacking when compared to other areas of mass spectrometry (MS). This paper examines the use laser‐induced dissociation and collision‐induced dissociation (CID) in MALDI–LIFT–ToF/ToF experiments to compare the usage of the two techniques on a range of polymeric analytes. It is demonstrated that for samples with an energetically preferable fragmentation pathway, such as those with a functional group in the backbone or a labile end group, post source decay (PSD) provides a simplified spectra with an increased pathway selectivity due to its utilization of metastable decay. This makes PSD a preferable technique for polymer sequencing, especially in low‐resolution time‐of‐flight techniques. Conversely, CID fragments less selectively, leading to higher intensity peaks from less favorable fragmentations. This makes CID more preferred for exact structural determination, such as finding the repeat unit structure. Abstract : Comparing the data produced by two common tandem mass spectrometry techniques on homopolymer and copolymer samples, it is found that post source decay produces a simplified fragmentation pattern when compared to collision‐induced dissociation, which allows for easier structural determination in lower‐resolution mass spectrometry techniques such as time‐of‐flight.